2015
DOI: 10.3345/kjp.2015.58.8.288
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gastric and other bowel perforations in preterm infants: a review of 20 years' experience in a single institution

Abstract: PurposeIn this study, we aimed to review the clinical presentation of preterm infants with gastrointestinal perforations and compare the clinical features of gastric perforation with other intestinal perforations.MethodsThe medical records of preterm neonates with pneumoperitoneum, admitted to the neonatal intensive care unit (NICU) between January 1994 and December 2013, were retrospectively reviewed.ResultsTwenty-one preterm infants underwent exploratory laparotomy to investigate the cause of the pneumoperit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 22 publications
3
19
0
2
Order By: Relevance
“…The birth weights of patients were ranged from 1500 to 3600 g. Gestational age of patients ranged from 30 to 40 weeks with an average of 36.03 ± 2.736 and the presentation-surgical intervention interval was 1-6 days (2.0±1.1). The predominance of males was clear in the current research and corresponding to findings of other works 18,19 , although the results of another research 17 showed increase in female percentage 15 (44.1%), the males still higher 19 (55.9%). The site of perforation showed a discrepancy from the esophagus extending to the colon, and the most frequent site in the present study was small intestine which corresponding to the pediatric literature, in which, the frequent site of GIP was the small bowels, and the distal ileum was the predominant [20][21][22] .…”
Section: Resultssupporting
confidence: 90%
“…The birth weights of patients were ranged from 1500 to 3600 g. Gestational age of patients ranged from 30 to 40 weeks with an average of 36.03 ± 2.736 and the presentation-surgical intervention interval was 1-6 days (2.0±1.1). The predominance of males was clear in the current research and corresponding to findings of other works 18,19 , although the results of another research 17 showed increase in female percentage 15 (44.1%), the males still higher 19 (55.9%). The site of perforation showed a discrepancy from the esophagus extending to the colon, and the most frequent site in the present study was small intestine which corresponding to the pediatric literature, in which, the frequent site of GIP was the small bowels, and the distal ileum was the predominant [20][21][22] .…”
Section: Resultssupporting
confidence: 90%
“…After retrospectively analyzing the clinical data, we found that most patients had a spontaneous gastric perforation, which was in accordance with other case reports. 8,16,17 Helicobacter pylori infection is thought to be highly associated with peptic ulcers, which might induce gastric perforation. However, gastric ulcer-induced perforation is uncommon in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that it is a full-term child of good weight, unlike most children who are affected by this pathology. Lee reviewed premature infants with perforations of the gastrointestinal tract, comparing gastric perforation with other sites [10]. He found five patients with gastric perforation and 11 with intestinal perforation.…”
Section: Discussionmentioning
confidence: 99%